2006
DOI: 10.1111/j.1469-8986.2006.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial stress‐induced increase in salivary alpha‐amylase is independent of saliva flow rate

Abstract: The stress response of salivary alpha-amylase (sAA) has been suggested as an index for sympathetic nervous system activation. However, concurrent inhibition of the parasympathetic nervous system is discussed as a confounder due to suppression of saliva flow rate. Here we set out to test the influence of stress-induced changes in flow rate on sAA secretion. Twenty-six subjects underwent the Trier Social Stress Test and a control condition. Saliva was sampled by passive drooling or salivettes. Saliva flow rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
195
3
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(219 citation statements)
references
References 39 publications
(74 reference statements)
11
195
3
10
Order By: Relevance
“…Considering the effect of flow rate on sAA, our results were in line with other studies by Beltzer et al 38 and Rohleder et al 34 wherein a positive correlation was observed between the alpha amylase levels (U/mL) and the alpha amylase outputs (U/min). In the study by Rohleder et al, 34 the effects of flow rate on sAA levels were examined in both baseline and stress conditions, and it was concluded that the sAA and sAA output responses to stress were significantly higher in both parameters; therefore, the stress response was the same irrespective of flow rate.…”
Section: Das Flow Rate and Saasupporting
confidence: 82%
See 2 more Smart Citations
“…Considering the effect of flow rate on sAA, our results were in line with other studies by Beltzer et al 38 and Rohleder et al 34 wherein a positive correlation was observed between the alpha amylase levels (U/mL) and the alpha amylase outputs (U/min). In the study by Rohleder et al, 34 the effects of flow rate on sAA levels were examined in both baseline and stress conditions, and it was concluded that the sAA and sAA output responses to stress were significantly higher in both parameters; therefore, the stress response was the same irrespective of flow rate.…”
Section: Das Flow Rate and Saasupporting
confidence: 82%
“…Previous literature by Nator et al, 16,18 , Nator and Rohleder 17 Rohleder et al, 34 Allwood et al, 35 and Kang et al 36 looked at the correlation between stress conditions, including psychological stress, and the levels of sAA. They all showed that stress causes a significant increase in sAA levels when patients were exposed to a stressful condition compared to a rest condition.…”
Section: Das Flow Rate and Saamentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva samples were stored at -20°C prior to analyses. The saliva samples were analyzed by the Kirschbaum lab, Technical University of Dresden (see Rohleder, Wolf, Maldonado, & Kirschbaum, 2006).…”
Section: Physiological and Subjective Measuresmentioning
confidence: 99%
“…Saliva samples were stored at −20°C prior to analyses. The saliva samples were analyzed by the Kirschbaum Lab, Technical University of Dresden (see Rohleder et al 2006). One person (from the propranolol group) had a missing saliva sample and three people (one from each group) had a missing alpha-amylase sample.…”
Section: Psychophysiological Measuresmentioning
confidence: 99%